Irreversible delayed complete heart block secondary to jailed first septal perforator following PCI of the left anterior descending coronary artery. - Sadiq, M.A.; Azman, W.; Abidin, I.Z. (2012)
Permanent complete heart block (CHB) secondary to the loss of first septal perforator after percutaneous coronary intervention (PCI) of the left descending artery (LAD) is an extremely rare complication. We describe a case report where a patient underwent PCI of proximal LAD, complicated by loss of first septal perforator, septal infarction, and bifasicular block, which progressed to symptomatic delayed CHB. One week later, the patient required implantation of a permanent pacemaker following failure to wean off the transvenous temporary pacing maker.